Is the Median Hourly Ambulatory Heart Rate Range Helpful in Stratifying Mortality Risk among Newly Diagnosed Atrial Fibrillation Patients? - Hsing-Yu Chen (MDPI AG, 2021)
Background: The application of heart rate variability is problematic in patients with atrial fibrillation (AF). This study aims to explore the associations between all-cause mortality and the median hourly ambulatory heart rate range (<semantics><mover accent="true">AHRR˜</mover>24hr</semantics>) compared with other parameters obtained from the Holter monitor in patients with newly diagnosed AF. Material and Methods: A total of 30 parameters obtained from 521 persistent AF patients’ Holter monitor were analyzed retrospectively from 1 January 2010 to 31 July 2014. Every patient was followed up to the occurrence of death or the end of 30 June 2017. Results:<semantics><mover accent="true">AHRR˜</mover>24hr</semantics> was the most feasible Holter parameter. Lower <semantics><mover accent="true">AHRR˜</mover>24hr</semantics> was associated with increased risk of all-cause mortality (adjusted hazard ratio [aHR] for every 10-bpm reduction: 2.70, 95% confidence interval [CI]: 1.75–4.17, p < 0.001). The C-statistic of <semantics><mover accent="true">AHRR˜</mover>24hr</semantics> alone was 0.707 (95% CI: 0.658–0.756), and 0.697 (95% CI: 0.650–0.744) for the CHA2DS2-VASc score alone. By combining <semantics><mover accent="true">AHRR˜</mover>24hr</semantics> with the CHA2DS2-VASc score, the C-statistic could improve to 0.764 (95% CI: 0.722–0.806). While using 20 bpm as the cut-off value, the aHR was 3.66 (95% CI: 2.05–6.52) for patients with <semantics><mover accent="true">AHRR˜</mover>24hr</semantics> < 20 bpm in contrast to patients with <semantics><mover accent="true">AHRR˜</mover>24hr</semantics> ≥ 20 bpm. Conclusions:<semantics><mover accent="true">AHRR˜</mover>24hr</semantics> could be helpful for risk stratification for AF in addition to the CHA2DS2-VASc score.